Activated ras Prevents Downregulation of Bcl-X(L) Triggered by Detachment from the Extracellular Matrix: A Mechanism of ras-Induced Resistance to Anoikis in Intestinal Epithelial Cells - Rosen, Kirill (The Rockefeller University Press, 2000)
Detachment of epithelial cells from the extracellular matrix (ECM) results in a form of apoptosis often referred to as anoikis. Transformation of intestinal epithelial cells by oncogenic ras leads to resistance to anoikis, and this resistance is required for the full manifestation of the malignant phenotype. Previously, we demonstrated that ras-induced inhibition of anoikis in intestinal epithelial cells results, in part, from the ras-induced constitutive downregulation of Bak, a pro-apoptotic member of the Bcl-2 family. Since exogenous Bak could only partially restore susceptibility to anoikis in the ras-transformed cells, the existence of at least another component of the apoptotic machinery mediating the effect of activated ras on anoikis was suggested. Indeed, here we show that, in nonmalignant rat and human intestinal epithelial cells, detachment from the ECM or disruption of the cytoskeleton results in a significant downregulation of the antiapoptotic effector Bcl-X(L), and that activated H- or K-ras oncogenes completely abrogate this downregulation. In addition, we found that enforced downregulation of Bcl-X(L) in the ras-transformed cells promotes anoikis and significantly inhibits tumorigenicity, indicating that disruption of the adhesion-dependent regulation of Bcl-X(L) is an essential part of the molecular changes associated with transformation by ras. While the ras-induced downregulation of Bak could be reversed by pharmacological inhibition of phosphatidylinositol 3 kinase (PI 3-kinase), the effect of ras on Bcl-X(L) was PI 3-kinase– and mitogen-activated protein kinase (MAP kinase)–independent. We conclude that ras-induced resistance to anoikis in intestinal epithelial cells is mediated by at least two distinct mechanisms: one that triggers downregulation of Bak and another that stabilizes Bcl-X(L) expression in the absence of the ECM.